2012
DOI: 10.1186/1471-2296-13-113
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-related prevalence of multimorbidity in primary care: the swiss fire project

Abstract: BackgroundGeneral practitioners often care for patients with several concurrent chronic medical conditions (multimorbidity). Recent data suggest that multimorbidity might be observed more often than isolated diseases in primary care. We explored the age- and gender-related prevalence of multimorbidity and compared these estimates to the prevalence estimates of other common specific diseases found in Swiss primary care.MethodsWe analyzed data from the Swiss FIRE (Family Medicine ICPC Research using Electronic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
82
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 17 publications
14
82
3
8
Order By: Relevance
“…With the increasing life expectancy worldwide, a higher proportion of individuals not only get older [1], but are also more likely to develop multiple chronic conditions [2][3][4]. Most chronic conditions (comorbidities) are covered by disease-specific clinical guidelines using a single disease framework; this leads physicians to recommend drug treatments for each condition separately, which may lead to polypharmacy and drug-drug and drug-disease interactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing life expectancy worldwide, a higher proportion of individuals not only get older [1], but are also more likely to develop multiple chronic conditions [2][3][4]. Most chronic conditions (comorbidities) are covered by disease-specific clinical guidelines using a single disease framework; this leads physicians to recommend drug treatments for each condition separately, which may lead to polypharmacy and drug-drug and drug-disease interactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…[19]. In all pain-associated cases in which patients consulted a German GP, nociceptive (musculoskeletal) pain dominates when compared with neuropathic pain -a fact that is quite analogous to other European data pooling: In Switzerland, chronic back pain with or without a radicular pain component is, aside from painful degenerative joint diseases, one of the most frequent reasons for consulting GPs [20]. According to a Swedish observational study [21], musculoskeletal pain disorders are found to be the most frequent reason to consult a doctor, with 21%, followed by respiratory diseases or hypertension.…”
Section: Introductionmentioning
confidence: 87%
“…This approach has previously been validated for the FIRE database [58,64]; All drugs prescribed for at least 6 months were considered to be long-term medication and counted as concomitant drugs; CHADS 2 -Score of stroke risk in patients with atrial fibrillation according to ICPC-2 coding was calculated according to Gage, et al [65]. We used the CHADS 2 -Score instead of the CHA 2 DS 2 -VASc-Score for comparison reasons, because the NOAC approval studies exclusively reported the CHADS 2 -Score.…”
Section: Patient Populationmentioning
confidence: 99%